2021
DOI: 10.1093/mnras/stab3062
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution deviation and the power suppression of baryons from dark matter

Abstract: The spatial distribution between dark matter and baryonic matter of the Universe is biased or deviates from each other. In this work, by comparing the results derived from IllustrisTNG and WIGEON simulations, we find that many results obtained from TNG are similar to those from WIGEON data, but differences between the two simulations do exist. For the ratio of density power spectrum between dark matter and baryonic matter, as scales become smaller and smaller, the power spectra for baryons are increasingly sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Moreover, by measuring the env-WCC in TNG100-1, we find that the dark matter and the gas in both the extreme dense (Δ  200) and underdense (Δ  0.1) environments always maintain very high correlation at all redshifts over a wide scale range, which qualitatively agrees with the findings in Farahi et al (2022) and Yang et al (2021). Particularly at the present epoch, the env-WCC is greater than 0.9 in densities of Δ  200 and Δ  0.1 at scales of k  10 h Mpc −1 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, by measuring the env-WCC in TNG100-1, we find that the dark matter and the gas in both the extreme dense (Δ  200) and underdense (Δ  0.1) environments always maintain very high correlation at all redshifts over a wide scale range, which qualitatively agrees with the findings in Farahi et al (2022) and Yang et al (2021). Particularly at the present epoch, the env-WCC is greater than 0.9 in densities of Δ  200 and Δ  0.1 at scales of k  10 h Mpc −1 .…”
Section: Discussionsupporting
confidence: 85%
“…On the simulation side, many studies have confirmed that the baryonic gas follows the underlying dark matter distribution on large scales quite well. For example, the power spectrum of the gas density field is very close to that of dark matter (e.g., Cui & Zhang 2017;Springel et al 2018), the spatial distributions of the dark matter and the baryonic gas are highly correlated with each other over a wide range of scales (e.g., Yang et al 2020Yang et al , 2021, and the gas alone can be used to classify the cosmic web in an unbiased manner (e.g., Cui et al 2018). Additionally, the intergalactic gas distribution is receiving increasing attention in observations.…”
Section: Introductionmentioning
confidence: 99%
“…Cui & Zhang 2017;Springel et al 2018), the spatial distributions of the dark matter and bary-onic gas are highly correlated with each other over a wide range of scales (e.g. Yang et al 2020Yang et al , 2021, and the gas alone can be used to classify the cosmic web un-biased (e.g. Cui et al 2018).…”
Section: Introductionmentioning
confidence: 99%